(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Effective Human Resource Management (HRM) plays a pivotal role in enhancing organizational performance. This abstract explores the critical connection between HRM practices and overall organizational success. HRM is integral to aligning workforce capabilities with organizational objectives, ensuring the right talent is in place. Talent acquisition, development, and retention strategies contribute significantly to building a skilled and motivated workforce. Employee engagement, a key focus of HRM, positively impacts productivity, innovation, and overall job satisfaction.Strategic workforce planning is paramount in anticipating and fulfilling future organizational needs. HRM practices, such as performance management and training programs, contribute to skill enhancement, promoting a culture of continuous improvement. The abstract also underscores the importance of effective communication, conflict resolution, and diversity and inclusion initiatives within HRM, as these factors contribute to a positive workplace environment.